Siri As a Tool for Speaking Practice: A Case Study of EFL Learner Interaction with Intelligent Assistants - Siddiq, Aditya Fadhilah; Sumarni, Sumarni (FKIP - Universitas Tanjungpura, 2025)
This study explored the experience of an EFL learner, Emily, a non-native English Speaker who has utilized Apple